ANALYSIS OF CORE COMPETENCY STRATEGIES IN HUMAN RESOURCES TO IMPROVE COMPANY PERFORMANCE AT PT WASKITA BETON PRECAST TBK - Muhammad Reyhan Yafi; Yayan Sudaryana; Mukhlis Catio (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the role of core competency strategies in human resources (HR) in improving company performance, with a case study at PT Waskita Beton Precast Tbk. The research focuses on three main aspects: identifying and analyzing the core competencies required in HR, strategies for managing core competencies in HR, and analyzing the relationship between core competencies in HR and company performance. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews and direct observation. The research results indicate that the development of core HR competencies, such as leadership, technological mastery, and results orientation, plays a significant role in improving company performance and operational efficiency. Management strategies encompassing continuous training, performance evaluation systems, and strengthening a collaborative work culture are key to reinforcing core HR competencies. The findings also indicate a strong correlation between effective management of core HR competencies and overall improvements in company performance, which contributes to achieving long-term competitive advantage.